Pengaruh Upah Minimum, Tingkat Partisipasi Angkatan Kerja (TPAK), dan Pendidikan terhadap Pengangguran: EKONOMI MAKRO - AMELIA AMELIA WANDA DHABITAH; Muhammad Sabandi; Dewi Kusuma Wardani (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
This study explores the influence of minimum wages, TPAK, and education levels on unemployment rates. The data analyzed covers the Solo Raya area for 2020-2024, designed to capture spatial and temporal variations between these variables. The study results indicate that minimum wages, TPAK, and education have no simultaneous influence on unemployment. This finding provides important implications for policy that the determination of minimum wages should consider productivity and regional conditions to avoid negative impacts on the labor market. Moreover, improving education and policies that encourage productive workforce participation can be effective strategies to reduce unemployment rates.